Delineating the Western Orders of Rights and Reason in Post‑Colonial Africa - Aswathi A. Nair (African Journal of Political Science)
Adherence to the fundamental tenets of Human Rights and advocacy of Democracy are the two traditionally entwined Western expressions of rights and reason that any state has to comply with to be treated as an egalitarian state. The degree of democratization in any state is to be gauged by its ability to give its citizens a fairly acceptable form of governance and a slew of natural rights and legal safeguards against human rights abuses, from which the idea of justice is to flow. Many of the African and Asian countries, that became sovereign states through the 1980s and 1990s and consequently came to be hailed as formal democracies, in reality, have only had a very perfunctory degree of democratization. In such circumstances, human rights, without the existence of a real democratic structure to uphold and sustain it, does not effectively translate into a charter of rights but would merely be retained as a set of flexible norms. It is in this context that the proposed paper intends to address the impact of globalization of the principles and values associated with the concepts of democracy and human rights in post-colonial African states. It also aspires to inquire into the need for an element of universality in the dialogues on human rights and democratization, so that they do not get reduced to mere synonyms for Westernization. Further, the reality and ambivalence surrounding the consolidation of democratic virtues along with the observance of human rights are best reflected in the exemplification of how the Sub-Saharan African country of Zimbabwe operated its “democracy”; both under its longest-serving President Robert Mugabe and post his unceremonious ouster following the coup d’etat on 14 November 2017. It would be interesting to study the political economy of transition in a country like Zimbabwe that, during and after its leading figure Mugabe, continues to pledge allegiance to a nationalist, post-colonial and populist anomaly of being principally antithetical to imperialism in all its forms while also being an anathema to the precepts of democracy, justice and human rights in practice.